Analysis of Overburden Structure and Pressure-Relief Effect of Hard Roof Blasting and Cutting - Hao Liu; Jin Dai; Jinquan Jiang; Pu Wang; Jiqiang Yang (Advances in Civil Engineering)
When studying the pressure-relief effect of hard roof blasting and cutting, the roof-cutting position and angle obviously affect the stability of the rock surrounding the gob-side entry (GSE). In this paper, control of the large deformation of rock surrounding the GSE is evaluated on the basis of the overlying structure and pressure-relief principle caused by roof cutting. Moreover, a mechanics model of a three-hinged arch structure (THAS) and a universal distinct element code (UDEC) numerical model with regard to the overlying rock movement were established to study the relationship among the rotation angle of key blocks in the THAS, the width of the roadway and the wall force beside it, and the optimal cutting position and cutting angle to reveal the pressure-relief effect of roof blasting and cutting and its influence on the support stability of the roadway. The results show that the overlying rock can form a stable THAS after roof blasting and cutting and that the wall stress and the coal-wall displacement are small, which indicates that roof blasting and cutting results in obvious pressure relief. The wall force increases with an increase in the rotation angle of the key block and decreases with an increase in the roadway width. Moreover, the optimal roof-cutting position (5 m) and angle (15°) are obtained with the specific mining conditions. Finally, on-site monitoring of the anchor-cable force and support force in panel 5312 of the Jining no. 3 coal mine is used to verify the pressure-relief effect after roof blasting and cutting. The study results can provide a theoretical basis for reasonable technical means and optimization of supporting parameters in field observation and have important application value for roof cutting and pressure relief for GSE retaining (GSER) technology.